THE RELATIONSHIP BETWEEN DIETARY ADHERENCE AND RANDOM BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS AT THE ANGGREK ELDERLY POSYANDU UNDER THE WORKING AREA OF BULULAWANG HEALTH CENTER - Sawitri, Diah Murni; Koesrini, Juliati; Roesardhyati, Ratna (Nurse and Health: Jurnal Keperawatan, 2025)
Background: Elevated blood glucose levels are indicative of type 2 diabetes mellitus, a metabolic disease. Glycemic stability is largely determined by dietary compliance, a crucial non-pharmacological treatment. Purpose: To determine how elderly clients with type 2 diabetes mellitus at the Anggrek Wellbeing Center in the Bululawang Community Health Center service area relate to random blood sugar levels and adherence to diet. Methods: A descriptive correlational quantitative technique and a cross-sectional strategy were used in this study. 54 elderly people with type 2 diabetes from the Anggrek Old Health Center comprised the study sample. This was obtained by use of the entire sampling approach. Diet compliance was measured using the PDAQ questionnaire, while blood sugar levels were measured using a glucometer. The relationship between the two variabels was analyzed using Pearson’s test. Results: Most participants had moderate to good dietary adherence (38.9% each), while 22.2% exhibited poor adherence. More than half of participants (57.4%) had normal RBG levels, while 42.6% had high levels. Dietary adherence and RBG showed a high and significant negative connection (r = –0.907, p = 0.000), suggesting that lower blood glucose levels were linked to improved adherence. Conclusion: Dietary adherence is essential for individuals with Type 2 diabetes in order to control their blood sugar levels at random. Strengthening dietary education and continuous monitoring is essential